Oligonucleotide aptamers: potential novel molecules against viral hepatitis - Mina Mirian; Hossein Khanahmad; Leila Darzi; Mansour Salehi; Hojjat Sadeghi-Aliabadi (Wolters Kluwer Medknow Publications, 2017)
Viral hepatitis, as an international public health concern, seriously affects communities and health system. In recent years, great strides have been taken for development of new potential tools against viral hepatitis. Among these efforts, a valuable strategy introduced new molecules called "aptamers". Aptamers as potential alternatives for antibodies could be directed against any protein in infected cells and any components of viral particles. In this review, we will focus on recent advances in the diagnosis and treatment of viral hepatitis based on aptamer technology. In recent years, various types of aptamers including RNA and DNA were introduced against viral hepatitis. Some of these aptamers can be utilized for early and precise diagnosis of hepatitis infections and other group selected as therapeutic tools against viral targets. Designing diagnostic and therapeutic platforms based on aptamer technology is a promising approach in viral infections. The obtained aptamers in the recent years showed obvious potential for use as diagnostic and therapeutic tools against viral hepatitis. Although some modifications to increase the biostability and half-life of aptamers are underway, it seems these molecules will be a favorable substitute for monoclonal antibody in near future.